Perubahan produktiviti dan kecekapan teknikal industri perkilangan elektrikal dan elektronik di Malaysia - Radam, Alias; Abu Mansor, Sazali; Adnan, Sarah Salwa (Universiti Putra Malaysia Press, 1999)
The interest on the study of productivity has continued to draw considerable passion among researchers due to the significant contribution of productivity to economic growth. The studies on productivity have not only focused on the techniques of measurement, but also the composition of productivity. Understanding the components of productivity offers important insights for policy makers into the sources of inefficiency among industries. By employing the DEA technique and Malmquist index, this study attempts to measure the productivity of the electrical and electronic industry. Through this technique, productivity can be decomposed into two, namely the technical change and efficiency change. The E&E sector has experienced an encouraging productivity growth through technical and efficiency changes.